1994
DOI: 10.4992/psycholres1954.36.94
|View full text |Cite
|
Sign up to set email alerts
|

Attentional modulation in motion aftereffect

Abstract: We examined the effects of concurrent alphanumeric discrimination task requiring the spatial selective attention to various motion aftereffects (MAE). We found that the effects of attentional tasks on the MAEs depended on the type of MAE and on the size of the adapting stimulus. For the small adapting stimulus, the strength of the simple translation MAE was attenuated by the concurrent tasks, and the MAE in depth or rotation MAE were not. Using the large stimulus, however, the effects of attention were not obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…the time constant). This finding is broadly consistent with Takeuchi & Kita (1994), who found that diverted attention led to reduced MAEs across adaptation durations of 20, 40 and 80 seconds.…”
Section: Adaptation Durationsupporting
confidence: 91%
See 4 more Smart Citations
“…the time constant). This finding is broadly consistent with Takeuchi & Kita (1994), who found that diverted attention led to reduced MAEs across adaptation durations of 20, 40 and 80 seconds.…”
Section: Adaptation Durationsupporting
confidence: 91%
“…They suggested that small vs. large (or whole field) stimuli are processed by separate motion mechanisms, with the former sensitive to object motion, and the latter sensitive to the optic flow generated by self-motion. Our analyses revealed smaller attentional effects for larger adaptation stimuli (which may be processed as optic flow), consistent with the idea that selective attention affects the processing of object, rather than self-motion (Takeuchi & Kita, 1994).…”
Section: Stimulus Sizesupporting
confidence: 87%
See 3 more Smart Citations